Splinters another kind of love story - Jamison, Leslie 1983- (Little, Brown and Company, 2024)
From the New York times best-selling author of The Recovering and The Empathy Exams comes the riveting story of rebuilding a life after the end of a marriage--an exploration of motherhood, art and new love
Keywords: Jamison, Leslie / 1983-; Women authors, American / 21st century / Biography; Single mothers / United States / Biography; Women; Écrivaines américaines / 21e siècle / Biographies; Mères de famille monoparentale / États-Unis / Biographies; Femmes; women (female humans); autobiographies (literary works); Autobiographies